Acupuncture: Effective and Recommended but More Implementation Needed - Mel Hopper Koppelman; Zhiheng GUO (Wolters Kluwer Health/LWW, 2024)
Abstract. Acupuncture enjoys a robust evidence base for dozens of clinical conditions and decades of research exploring its mechanisms of action. It has over 9,000 positive recommendations from official government and clinical guidelines. However, it still remains relatively inaccessible in the United States, Europe and elsewhere, especially compared to the strength of evidence-based recommendations for its use. Acupuncture would benefit from robust implementation strategies, utilizing insights and approaches from implementation science. The clinical use of Botox for migraine suffered from weaker evidence of effectiveness and greater evidence of harm, but using a streamlined and robust implementation strategy, Allergan was able to achieve widespread implementation from when it began its efforts around 2010. Such a systematic approach that identifies and overcomes barriers to implementation for acupuncture would benefit millions of people who currently are offered less effective and more invasive treatments, contrary to the recommendations of clinical guidelines.